Certifications for agribusiness with huge export potential - Julio Bautista, Gladys (Universidad Francisco de Paula Santander, 2015)
The moral principles of the religions (in this case the Abrahamic religions) also define the lifestyles of their followers, including aspects related to food, marking the way of consumption of these communities; The Kosher and Halal certifications are quality seals, where a Jewish and Muslim authority approves that the company meets the requirements for food processing and / or the product is suitable for human consumption, as they meet the requirements of the religious rules governing these communities; This would seem to be a mere whim to satisfy a small group of consumers in Colombia, given that the Jewish and Muslim communities are very small, but it is not so, these seals open the doors to new markets, which could be interested in importing national products, this is how prestigious companies have obtained these certifications, achieving excellent results, since the vast majority of their national consumers do not belong to the religious communities mentioned.